Ways of Choosing: The Role of School Design Culture, Values and Philosophy in Irish Architectural Education (EAAE Annual Conference Proceedings, 2019)
Architectural education in Ireland — as elsewhere — is a somewhat unique educational environment in that it must provide for professional requirements within its system. It must produce graduates which have demonstrated standards of knowledge, skill and competence for practice as an architect and who possess particular professional attributes. Coupled with this framework, architectural education is also required to instil in students their civic responsibilities, in being bound by professional codes of ethics to act and to build in a way that has societal values at its heart; considering the interests of society as a whole (1) to shape a better world. As such, graduates are taught to question and direct design conditions from particular points of view (2) and to create ‘good’ architecture through the application of dependable professional education (3). The content and subject matter of architectural courses must therefore be both creative and technical, freeing and curtailing, locally responsive but universally applicable.
Keywords: design culture; values in design; sustainable design excellence; design process; sustainability in design education